Growth and age composition of the South African maasbanker Trachurus trachurus Linnaeus, 1950-1969 - Geldenhuys, N. D (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1971.